Regorafenib-induced hypothyroidism and cancer-related fatigue: is there a potential link?. Issue 1 (July 2017) - Pani, Fabiana; Massidda, Matteo; Pusceddu, Valeria; Puzzoni, Marco; Massa, Elena; Madeddu, Clelia; Scartozzi, Mario; Mariotti, Stefano
Abstract : Objective: Thyroid dysfunction has been reported during Regorafenib (Reg) administration, but no detailed study is presently available. Design: Prospective, observational cohort study. Patients with documented metastatic colorectal cancer and progression of disease during or within 3 months after the last standard therapy, with no evidence and history of previous thyroid disease were enrolled. Methods: Twenty-five consecutive patients were evaluated before and 8–50 weeks after initiating Reg therapy by monthly clinical, ultrasound and laboratory (thyrotropin (TSH), free thyroxine (fT4), antithyroglobulin (TgAb) and antithyroid peroxidase (TPOAb)) evaluation. Results: Thirteen/25 patients (52%) became hypothyroid (TSH: 12.5 ± 4.01 IU/L, range: 4.6–22.0) within 5 months of therapy. TPOAb became detectable (99–155 IU/mL) in 2/25 (8%) patients. Thyroid volume progressively decreased (from 8.6 ± 2.2 mL to 4.9 ± 2.4 mL after 5 months of Reg therapy, P < 0.0001). The progression-free survival (PFS) was longer in patients developing hypothyroidism (43 weeks) than in those remaining euthyroid (17 weeks, P < 0.01). Fatigue (the most common general serious Reg adverse event) was associated with hypothyroidism severity and reversed after levothyroxine therapy (L-T4). Conclusions: Reg rapidly causes hypothyroidism in about 50% of patients and in a minority of them also triggers thyroid autoimmunity. Reg-induced hypothyroidism was strictly related to fatigue, easily reversed by L-T4 administration and associated to longer survival. These results suggest that prompt recognition of hypothyroidism in patients with severe fatigue may prevent unnecessary Reg dose reduction or withdrawal.